How Do Different Generations Communicate on Social Media? A Comparative Analysis of Language Styles, Emoji Usage, and Visual Elements - Inamul Azad; Sugandha Chhibber; Azra Tajhizi (Language, Technology, and Social Media, 2023)
This study aims to explore generational differences in language styles on social media, with a focus on levels of formality, emoji usage, and the integration of visual communication elements. A quantitative content analysis was conducted on a sample of 4,000 social media posts collected from Twitter, Facebook, and Instagram. The sample included posts from four generational cohorts: Baby Boomers, Generation X, Millennials, and Generation Z. Each post was analyzed for language structure, the frequency of emoji use, and the presence of visual elements such as memes. Statistical methods, including ANOVA, were employed to identify significant differences across generations. The analysis revealed that Baby Boomers prefer more formal language structures, reflecting their adherence to traditional communication norms. In contrast, Generation Z demonstrates a strong preference for informal language, frequent use of abbreviations, emojis, and memes, illustrating their adaptation to the fast-paced, visually-oriented nature of digital communication. The study concludes that these generational differences are shaped by both cultural background and technological exposure, leading to distinct communication patterns across age groups. This research contributes to the field of digital communication by providing empirical evidence on how generational cohorts interact differently on social media, offering valuable insights for marketers and digital strategists in tailoring their communication strategies.